The Role of Malocclusion and Oral Parafunctions in Predicting Signs and Symptoms of Temporomandibular Disorders-A Cross-Sectional Study - Luka Šimunović; Marina Lapter Varga; Dubravka Negovetić Vranić; Ivana Čuković-Bagić; Lana Bergman; Senka Meštrović (MDPI AG, 2024)
Background: The aim of this study was to examine to what extent malocclusion and parafunctional habits contribute to the development of signs and symptoms associated with temporomandibular disorders (TMD) in schoolchildren with mixed dentition in Croatia in a sample of 338 children, aged 9 to 15 years. Methods: TMD signs and symptoms assessed by the clinician were joint function and pain, masticatory muscles tenderness, range of mandibular motion, and joint sounds. To evaluate subjective symptoms and parafunctions, children and parents were asked about the presence of headaches, jaw locking, temporomandibular joint (TMJ) sounds, pain during mouth opening, or bruxism, as well as parafunctions like biting pencils or nails, chewing hard candies or ice, daily gum chewing, opening bottles with teeth, engaging in jaw play, thumb-sucking, and clenching/grinding teeth. Results: At least one symptom of a TMD was pronounced in 142 participants (42.0%). The most commonly reported parafunction was pencil or nail biting, present in 25.1% of participants. Class II malocclusion increased the likelihood by 2.6 times, pencil or nail biting by 2.34 times, and clenching/grinding teeth by 8.9 times that the subject would exhibit at least one TMD symptom. Conclusions: Every child with mixed dentition should undergo a brief examination of the TMJ, especially in cases of Class II malocclusion, pencil or nail biting, and teeth clenching or grinding, as these have all been identified as significant risk factors that increase the likelihood of experiencing TMD symptoms. This highlights the need for proactive screening and assessment by healthcare providers to reduce the risk and prevalence of TMDs in affected children and ensure timely diagnosis and treatment.